2019
DOI: 10.1101/cshperspect.a036368
|View full text |Cite
|
Sign up to set email alerts
|

Multitasking Kinase RIPK1 Regulates Cell Death and Inflammation

Abstract: Receptor-interacting serine threonine kinase 1 (RIPK1) is a widely expressed kinase that is essential for limiting inflammation in both mice and humans. Mice lacking RIPK1 die at birth from multiorgan inflammation and aberrant cell death, whereas humans lacking RIPK1 are immunodeficient and develop very early-onset inflammatory bowel disease. In contrast to complete loss of RIPK1, inhibiting the kinase activity of RIPK1 genetically or pharmacologically prevents cell death and inflammation in several mouse dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 205 publications
0
49
0
Order By: Relevance
“…PGRN abundance is modulated in response to RIPK1-mediated phosphorylation [118], whose activation can sense viral or toxic nucleotides via the toll-like receptor TLR3 [93, 129], drives pro-inflammatory necroptosis [234], and is implicated in ALS [81, 230]. Consistent with these reports, enhanced RIPK1 protein levels were observed in the spinal cord of Atxn2 -CAG100-KIN mice, possibly with a 1.4-fold abundance already at 3 months, but achieving significance only for the 1.5-fold increase at the age of 14 months (Figure 3C/D).…”
Section: Resultsmentioning
confidence: 99%
“…PGRN abundance is modulated in response to RIPK1-mediated phosphorylation [118], whose activation can sense viral or toxic nucleotides via the toll-like receptor TLR3 [93, 129], drives pro-inflammatory necroptosis [234], and is implicated in ALS [81, 230]. Consistent with these reports, enhanced RIPK1 protein levels were observed in the spinal cord of Atxn2 -CAG100-KIN mice, possibly with a 1.4-fold abundance already at 3 months, but achieving significance only for the 1.5-fold increase at the age of 14 months (Figure 3C/D).…”
Section: Resultsmentioning
confidence: 99%
“…These developments have sparked a large number of studies addressing the mechanisms regulating the different types of regulated cell death and their role in physiology and disease, which have been covered in a number of comprehensive reviews during the last years [3,5,[8][9][10]. The aim of the present short article is not to comprehensively cover the large literature on cell death, but rather to discuss most recent studies that shed light on new mechanisms regulating and connecting necroptosis and pyroptosis, focusing particularly on the role of caspase-8 and RIPK1 as essential players in a complex network of cell death signalling.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in RIPK1deficient mice and cells showed that RIPK1 acts as a scaffold independently of its kinase activity to regulate pro-inflammatory and pro-survival TNFR1 and TLR3/4 signaling, a function that is essential for mouse development and tissue homeostasis [3][4][5][6][7][8][9][10] . In contrast, RIPK1 kinase activity induces cell death by activating either caspase-8-dependent apoptosis or RIPK3-mixed lineage kinase like (MLKL)-dependent necroptosis 1,2,11,12 . Multiple studies using genetic or pharmacological inhibition have identified RIPK1 kinase activity-dependent cell death as a potent trigger of inflammation in different tissues [13][14][15][16][17] .…”
mentioning
confidence: 99%